Handbook of Adult and Continuing Education. - Wilson, Arthur L. (John Wiley & Sons, Inc., 2009)
Sponsored by the American Association of Adult & Continuing Education"This monumental work is a testimony to the science of adult education and the skills of Wilson and Hayes. It is a veritable feast for nourishing our understanding of the current field of adult education. The editors and their well-chosen colleagues consistently question how we know and upon what grounds we act. They invite us to consider not only how we can design effective adult education, but also why we practice in a particular socio-economic context.". - Resumé vydavatel
Keywords: vzdělávání dospělých; další vzdělávání; adult learning; continuing education; elektronické knihy; sborníky; electronic books; papers of several authors